Kajian Sosiologi Penetapan Sanksi Terhadap Tindak Pidana Pencurian Putusan 312/Pid.B/2021/PN Psp di Pengadilan Negeri Padangsidimpuan - Halima, Halima; Gunawan, Syafri (Jurnal El-Thawalib, 2023)
The problem in this research is the Sociological Study of the Determination of Sanctions for the Crime of Theft Decision 312/Pid.B/2021/PN Psp at the Padangsidimpuan District Court, this type of research is literature with a qualitative approach. The primary data source in this study is the judge's decision in case No. 312/Pid.B/2021/PN Psp, and the secondary data source is books, journal articles and documents related to this research. data collection technique is document study, data analysis technique is descriptive. The results of this study indicate that the judge's consideration in case No. 312/Pid.B/2021/PN Psp is the first is the element of the owner of the goods, the second is the element of intent in theft and the third is the element of possessing goods against rights and which becomes a factor for the judge's consideration is the firstly juridical factors, philosophical factors and sociological factors.